2011
DOI: 10.4028/www.scientific.net/amr.243-249.4596
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Cemented Sand and Gravel Constitutive Model

Abstract: Basing on triaxial experiments, the paper conducts the research to Cemented Sand and Gravel constitutive model. Using virtual rigid spring method, the Cemented Sand and Gravel constitutive model with considering the softening characteristics of material is established, and parameters needed are determined, the model establishes the foundation of non-linear analysis of Cemented Sand and Gravel structure. Mechanical properties and constitutive model study of Cemented Sand and Gravel is key to Cemented Sand and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…At this stage, the deviatoric stress (σ 1 − σ 3 ) decreases as the axial strain increases, and the tangent elastic modulus is negative at this time. Therefore, the classical hyperbolic model cannot be directly used [18]. Curve 1 in Figure 4a is the actual stress-strain curve of the material, and the stressstrain relationship at this time does not satisfy the classical hyperbolic model.…”
Section: Principle Of Virtual Rigid Spring Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, the deviatoric stress (σ 1 − σ 3 ) decreases as the axial strain increases, and the tangent elastic modulus is negative at this time. Therefore, the classical hyperbolic model cannot be directly used [18]. Curve 1 in Figure 4a is the actual stress-strain curve of the material, and the stressstrain relationship at this time does not satisfy the classical hyperbolic model.…”
Section: Principle Of Virtual Rigid Spring Methodsmentioning
confidence: 99%
“…At this stage, the deviatoric stress (𝜎 1 − 𝜎 3 ) decreases as the axial strain increases, and the tangent elastic modulus is negative at this time. Therefore, the classical hyperbolic model cannot be directly used [18].…”
Section: Principle Of Virtual Rigid Spring Methodsmentioning
confidence: 99%
“…Many advisable explorations have been made on the constitutive model of CSG. Sun et al [ 29 ] found a nonlinear elastic model based on the augmented spring method. Alan et al [ 30 ] proposed an elastic-plastic yield model considering the viscosity effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in the world practice of hydraulic engineering construction, there has been a trend in the design of combined dam structures. At the same time, new designs of concrete dams appear, including soil elements -dams made of soil concrete (CSG) [1][2][3], at the same time, elements made of cement, concrete and reinforced concrete materials appear in the designs of soil dams. The emergence of new dam designs is caused by the expansion of construction regions, covering the territories of the Northern climatic zone, foothills and mountainous regions, where there is often no developed transport infrastructure, there are no quarries of special building materials, where the conditions for conducting construction work and skipping construction costs are complicated,…”
Section: Introductionmentioning
confidence: 99%